Maori Origins and Migrations : the Genesis of Some Pakeha Myths and Legends. - Sorrenson, M. P. K. (Auckland University Press, 2013)
Since Europeans first set foot in New Zealand they have speculated about where the Maori people came from, how they made their way to New Zealand and how they lived when they arrived here. Theories have abounded: some of them have hardened into accepted truth. The result has been an accumulation of Pakeha myths about Maori origins. The process of this mythmaking is the subject of Sorrenson's book: 'It is not an attempt to find an original or even a Pacific homeland for the Maori. I leave that task to the many others who are happily engaged on it.' But as a study of the development o.